Modulation of Growth Performance and Intestinal Microbiota in Chickens Fed Plant Extracts or Virginiamycin - Zhu, Nianhua; Wang, Jun; Yu, Longfei; Zhang, Qiman; Chen, Kai; Liu, Baosheng (Frontiers in Microbiology, 2019)
In this study, the effects of plant extracts and virginiamycin on broiler growth performance, as well as on host intestinal microbiota composition and function were investigated. A total of 288 one-day-old male Cobb broiler chickens were randomly divided into four treatment groups. The duodenal, ileal, and cecal content of six broilers per treatment group after 14 and 28 days of treatment were sampled. This material was used for high-throughput Illumina sequencing of the V3–V4 region of the 16S rRNA gene. The results showed that chickens fed 400 mg/kg plant extracts (HPE group) had significantly higher average body weights at d28 as compared to the control group (CT; P < 0.05), and lower feed-to-meat ratios over days 15–42 (P < 0.01). Within the HPE group at day 14, the relative abundances of two bacterial phyla and 10 bacterial genera increased significantly in the ileal microbiota, and the relative abundance of three bacterial phyla and four bacterial genera decreased. The relative abundance of the genus Lactobacillus in the cecal microbiota decreased from 21.48% (CT group) to 8.41% (fed 200 mg/kg PEs; LPE group), 4.2% (HPE group), and 6.58% (fed 30 mg/kg virginiamycin; VIRG group) after 28 days. In contrast, Faecalibacterium and unclassified Rikenellaceae increased in abundance in the HPE group (from 18% to 28.46% and from 10.83% to 27.63%, respectively). PICRUSt function analysis showed that the ileal microbiota of the PE treatment groups were more enriched in genes related to the metabolism of cofactors and vitamins. In addition, the cecal microbiotas of the LPE and HPE groups were enriched in genes predicted to encode enzymes within 15 and 20 pathways, respectively. These pathways included protein digestion and absorption, amino acid metabolism, lipid biosynthesis, lipopolysaccharide biosynthesis, the citrate cycle, and lipoic acid metabolism. Similarly, the VIRG group was enriched in 55 metabolic pathways (17 in the duodenum, 18 in the ileum, and 20 in the cecum) on d 28 (P < 0.05). Thus, the results indicated that the observed increase in broiler growth performance after PE or VIRG supplementation might be attributed to an improvement in intestinal microbial composition and metabolic function.